Wokół imienia i nazwiska Jubilata – nazwy osobowe w perspektywie lingwistyki kulturowej - Rudnicka-Fira, Elżbieta (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The author of the texts undertakes an onomastic analysis of the name Edward and the surname Stachurski. She enriches her deliberations with statistic data and remarks on the historic determinants of forming the proper names in Poland.asymmetry that could be the verbal evidence of “fighting with obesity.”